2013
DOI: 10.1038/ncb2861
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β2 dictates disseminated tumour cell fate in target organs through TGF-β-RIII and p38α/β signalling

Abstract: In patients non-proliferative disseminated tumour cells (DTCs) can persist in the bone marrow (BM) while other organs (i.e. lung) present growing metastasis. This suggested that the BM might be a metastasis “restrictive soil” by encoding dormancy-inducing cues in DTCs. Here we show in a HNSCC model that strong and specific TGFβ2 signalling in the BM activates p38α/β, inducing a [ERK/p38]low signalling ratio. This results in induction of DEC2/SHARP1 and p27, downregulation of CDK4 and dormancy of malignant DTCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
494
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(535 citation statements)
references
References 49 publications
(60 reference statements)
39
494
1
1
Order By: Relevance
“…A recent study showed that transforming growth factor-β2 (TGFβ2) was effective in promoting the upregulation of p27 and p38 by the SMAD1/2/5 pathway in tumor cells undergoing a dormant state [31]. Lactic acid was shown to induce both transcription and protein secretion of TGFβ2 in glioma cells [32] and to induce TGFβ1 production in in vivo model [33].…”
Section: How Low Ph May Contribute To Dormancy Of Tumor Cells Aciditymentioning
confidence: 99%
“…A recent study showed that transforming growth factor-β2 (TGFβ2) was effective in promoting the upregulation of p27 and p38 by the SMAD1/2/5 pathway in tumor cells undergoing a dormant state [31]. Lactic acid was shown to induce both transcription and protein secretion of TGFβ2 in glioma cells [32] and to induce TGFβ1 production in in vivo model [33].…”
Section: How Low Ph May Contribute To Dormancy Of Tumor Cells Aciditymentioning
confidence: 99%
“…Epithelial hyperplasia has been seen in some animal models, including tumor-promoting effects of LY2109761 in renal cell carcinoma (RCC) (Laping et al 2007). There have also been preclinical reports of the ability of TGF-b blockade drugs to awaken dormant metastatic breast tumor cells within the bone marrow, with the supposition that TGF-b2 plays a major role in breast tumor cell dormancy (Bragado et al 2013). During a clinical trial of the pan anti-TGF-b antibody, fresolimumab, for the treatment of endstage drug-refractile metastatic melanoma and RCC, grade 1 or 2 skin rashes that improved or resolved by the end of study were reported in 10 of 29 patients, and nonmalignant keratoacanthomas (KA) appeared de novo in four of these patients (Morris et al 2014), whereas a lowgrade SCC appeared in another individual (Lacouture et al 2015).…”
Section: Monitoring and Prevention Of Tgf-b Blockade-induced Drug Toxmentioning
confidence: 99%
“…The BMP/TGFb pathway has been previously implicated in restricting cancer metastasis development. [15][16][17][18][19][20] Thus, it has been reported that BMP7 could inhibit formation of bone but not loco-regional lymph node metastases by human prostate cancer cells inoculated in nude mice. 17 In a subsequent study, expression of the BMPR2 receptor (that can bind BMP4 or BMP7) in prostate cancer cells was inversely correlated with bone metastasis and recurrence in men and required for the quiescence of cancer stem cells.…”
Section: Respective Contribution Of Low Cell Density and Hypertonicitmentioning
confidence: 99%
“…These pathways could allow determining how cell intrinsic features and environmental interactions can lead to metastasis development. [15][16][17][18][19][20][21][22] However, a detailed analysis of dormancy has been hampered by the challenge of identifying and studying dormant cells in vivo. Therefore, models of dormancy in cell culture have been developed which rely on the parallel between metastasis in vivo and the clonogenic capacity in vitro, i.e.…”
Section: Introductionmentioning
confidence: 99%